The transcription factor GmNAC018 confers salt tolerance in soybean - Zhao, Lianjia; Li, Xingang; Wang, Peiguo; Hao, Weiwei; Li, Gan; Li, Chunyan; Liao, Daolong; Wen, Ke (Frontiers in Plant Science, 2026)
Soybean (Glycine max) plays a vital role in global food security and nutrition but faces increasing threats from soil salinization, an expanding environmental issue that affects approximately 1.38 billion hectares of land worldwide. Plants possess a diverse array of genes that facilitate adaptation to salt stress. Transcription factors are central regulators in mediating this response. They coordinate the physiological process that enables plants to adapt to high-salt environments by regulating the expression of downstream genes. The present study examines the function of the GmNAC018 gene in improving salt tolerance in soybean. We generated transgenic soybean plants with overexpression and observed improved germination, higher chlorophyll content, increased biomass, and lower sodium ion accumulation under salt stress compared to wild-type plants. The overexpression of GmNAC018 resulted in increased expression of key salt-tolerance genes, demonstrating its involvement in activation of the salt stress response pathway. Our results also suggest that GmNAC018 may be a key gene in regulating salt tolerance in soybean, providing theoretical molecular support for understanding the salt tolerance regulation mechanism in plants.